Unfavourable prognosis of patients with trisomy 18q21 detected by fluorescence in situ hybridisation in t(11;18) negative, surgically resected, gastrointestinal B cell lymphomas. Issue 4 (26th March 2004) - Krugmann, J; Tzankov, A; Dirnhofer, S; Fend, F; Greil, R; Siebert, R; Erdel, M
Abstract : Background: The most frequent cytogenetic alteration in gastrointestinal (GI) B cell lymphoma (BCL) is t(11;18)(q21;q21). GI B cell non-Hodgkin lymphomas lacking this translocation vary in their biology and clinical outcome. The t(11;18) negative subgroup shows increased numerical changes of chromosome 18, although its clinical relevance remains unknown. Methods: Thirty surgically resected primary GI BCLs were examined—11 low grade marginal zone mucosa associated lymphoid tissue (MALT) lymphomas, four marginal zone lymphomas with diffuse large BCL (DLBCL), and 15 de novo DLBCLs. Chromosome 18 aberrations were examined using interphase fluorescence in situ hybridisation. Trisomy 18 was studied applying a centromere 18 probe and a dual colour probe for the MALT1 gene at 18q21. Results: Using the MALT1 probe, only one marginal zone MALT lymphoma had a break apart pattern, indicating t(11;18) or variants. In the GI BCLs lacking MALT1 breaks, trisomy 18q21 was seen in seven patients (four with complete trisomy 18 and three with partial trisomy of 18q21). Trisomy 18q21 was found in two of 10 low grade MALT lymphomas and five of 19 GI BCLs with large cell component. Six of 17 patients with trisomy 18q21 presented with ≥stage II and one of 12 with stage I disease. Trisomy 18q21 was associated with significantly shorter disease specific survival in the whole group and GI BCLs with large cell component, but not in the low grade group. Conclusions: Trisomy 18q21, including MALT1, may be associated with advanced tumour stage and may be a predictor of poor outcome in surgically resected primary GI BCLs.